Los Baldecitos (San Juan, Argentina) as the portal of the Ischigualasto Provincial Park(World Heritage Site): enhancement of the tangible and intangible cultural heritage - Andrada, Yamila Vanesa (2020)
The tourism potential is analyzed, in relation to the tangible and intangible cultural heritage, of Los Baldecitos locality, adjacent to the Ischigualasto Provincial Park. To do this, the points of interest were inventoried, aspects of the intangible heritage were rescued, information on the tourist acommodations and infrastructure was collected, an inquiry was made about the interest of tourists and residents for initiatives in the locality, and strengths, opportunities, weaknesses, strengths and threats were analyzed, considering the information obtained in the scenario of the current pandemic. Los Baldecitos has the resources to make an interesting offer. The challenges are related to the lack of maintenance of the points of interest, the lack of support from private and state organizations, and the impact of the COVID-19 pandemic. The Ischigualasto Provincial Park is the most visited protected area in the province and with much promotion at the national level, but the «spillover effect» of the benefits does not reach Los Baldecitos. It is necessary that the residents make the decision to put projects in motion and that the benefits that emanate from the close relationship with the park and the new global trend towards the recovery of tourism through sustainability, are materialized with subsidies and technical support for the initiatives of the villagers.